2018
DOI: 10.1016/j.jor.2018.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Association of MTHFR and TNF-α genes polymorphisms with susceptibility to Legg-Calve-Perthes disease in Iranian children: A case-control study

Abstract: Our case-control study failed to determine any association of MTHFR (677C > T and 1298A > C) and TNF-α (-308G > A and -238G > A) polymorphisms with LCPD risk. More studies with larger sample size are warranted to validate our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…TNF-α is a potential pro-inflammatory cytokine, which plays a critical role in a wide range of inflammatory, malignancies, and autoimmune diseases (10,11) . The TNF-α gene is located on chromosome 6p21.3, contains 8 exons, and encodes 382 amino acids (12,13) . The human TNF-α gene has close linkage with HLA class I and class II (8) .…”
Section: Association Of Tnf-α -308g>a Polymorphism With Susceptibilitmentioning
confidence: 99%
“…TNF-α is a potential pro-inflammatory cytokine, which plays a critical role in a wide range of inflammatory, malignancies, and autoimmune diseases (10,11) . The TNF-α gene is located on chromosome 6p21.3, contains 8 exons, and encodes 382 amino acids (12,13) . The human TNF-α gene has close linkage with HLA class I and class II (8) .…”
Section: Association Of Tnf-α -308g>a Polymorphism With Susceptibilitmentioning
confidence: 99%
“…Epidemiological studies had identified that Methylene tetrahydrofolate reductase (MTHFR) was a potential genetic marker of different malignancies (Yi et al, 2016;He and Shen, 2017). The human MTHFR gene is located on chromosome 1p36.3, consist of 11 exons and spans 2.2 kb of genomic DNA (Abedinzadeh et al, 2015;Azarpira et al, 2018). It is encodes the vital enzyme which plays a key role in the folate/homocysteine metabolic pathway and regulates the intracellular folate level for the synthesis and methylation of DNA (Azarpira et al, 2018;Kamali et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The human MTHFR gene is located on chromosome 1p36.3, consist of 11 exons and spans 2.2 kb of genomic DNA (Abedinzadeh et al, 2015;Azarpira et al, 2018). It is encodes the vital enzyme which plays a key role in the folate/homocysteine metabolic pathway and regulates the intracellular folate level for the synthesis and methylation of DNA (Azarpira et al, 2018;Kamali et al, 2018). In humans, the MTHFR 677C>T (in exon 4) polymorphism has been heavily studied in different disease.…”
Section: Introductionmentioning
confidence: 99%
“…In past decades, apart from genetic variations that have raised major concerns in cancer bio logy, the role of inflammation factors such as tumour necrosis factor-alpha (TNF-α) has been widely researched in the aetiology of cancer [10,11]. The human TNF-α gene located on chromosome 6p21.3 contains 8 exons and encodes 382 amino acid proteins, in which -308G>A and -238 G>A are the most common polymorphisms [12,13]. TNF-α is a potential pro-inflammatory cytokine, which plays a critical role in a wide range of inflammatory, autoimmune and malignant diseases.…”
Section: Introductionmentioning
confidence: 99%